The equation x

For ax

x = (-b ±√(b

Your equation has a=1, b=-5, c=-24.

x = (-(-5) ±√((-5)

= (5 ±√(25 + 96))/2 = (5±√121)/2 = (5±11)/2

x = 16/2 or -6/2

x = 8 or -3

^{2}- 5x - 24 = 0 can be factored as (x-8)(x+3) = 0, so we know the solutions are x=8 and x=-3. Here's the solution using the quadratic formula.For ax

^{2}+bx+c = 0, the solutions are given byx = (-b ±√(b

^{2}-4ac))/(2a)Your equation has a=1, b=-5, c=-24.

x = (-(-5) ±√((-5)

^{2}- (4)(1)(-24))/(2*1)= (5 ±√(25 + 96))/2 = (5±√121)/2 = (5±11)/2

x = 16/2 or -6/2

x = 8 or -3